A phase 2 study of ofatumumab (Arzerra®) in combination with a pan-AKT inhibitor (afuresertib) in previously treated patients with chronic lymphocytic leukemia (CLL)*. Issue 1 (2nd January 2019) - Chen, Christine I.; Paul, Harminder; Le, Lisa W.; Wei, Ellen N.; Snitzler, Susi; Wang, Trina; Levina, Olga; Kakar, Sumeet; Lau, Anthea; Queau, Michelle; Johnston, James B.; Smith, Deborah A.; et al.
Abstract: AKT plays a centralized role in tumor proliferation and survival and is aberrantly activated in chronic lymphocytic leukemia (CLL). In this phase 2 trial, 30 relapsed/refractory CLL patients were treated with combination afuresertib, a novel oral AKT inhibitor, and ofatumumab for 6 months, followed by afuresertib maintenance for 12 months. We aimed to achieve deeper and more durable responses, without requiring long-term continuous treatment. Treatment was generally well tolerated but respiratory infections were common, with 18% severe requiring hospitalization. Hematologic toxicities were manageable (grade 3–4 neutropenia 39%). At a median follow-up of 13.4 months, overall responses were 50% (complete responses 3.6%). Median progression-free survival was 8.5 months and overall survival 34.8 months. Combination therapy with ofatumumab and afuresertib is active and well tolerated, but does not appear to lead to durable responses and may not provide additional benefit over single-agent ofatumumab in relapsed/refractory CLL. Novel agent combinations are currently undergoing intense investigation.